Mathematical Modeling of the Gas Dynamic Parameters of Impinging Heat-Transfer Medium Jet in Borehole Thermal Reaming Process - Bulat, A.F.; Voloshyn, O.I.; Potapchuk, I.Yu.; Yemelianenko, V.I.; Zhovtonoha, M.M.; Zhevzhyk, O.V.; Manigandan, S. (Science and Innovation, 2024)
Introduction. As compared with other ways of thermal destruction of rocks, the rock destruction by low temperature plasma jet has advantage in terms of distribution of cracks in rock at a considerable depth, high heat transfer coefficient and high specific heat flux, simplified system of automation and remote control, and compactness of thermal tool. Problem Statement. Thus, the possibilities of analytical determination of optimal parameters of thermal effect on rocks are limited by solution of thermoelasticity equations and contact problems of strength theory. Such formulation of the problem is unacceptable due to complication of taking into account substantial changes in the physical and thermos-physical rock properties while heating and applying mechanical load. Due to abovementioned facts it is obviously necessary to develop a mathematical model that enables to define basic gas dynamic jet parameters of heat-transfer medium in the process of borehole thermal reaming. Purpose. The purpose of this research is to develop a mathematical model for calculating the gas dynamic characteristics (pressure, density, and velocity) of the heat-transfer medium while it is moving along the surface of the borehole in the thermal reaming process. Materials and Methods. Mathematical modeling of the flow process for free and impact jets of heat-transfer medium using a PC. Results. Experimental studies have confirmed adequacy of the developed mathematical model for calculation of gas dynamic characteristics (pressure, density, and velocity) of the heat-transfer while it is moving along the surface of the borehole in the process of its thermal reaming. Conclusions. The obtained results can be used for modeling the gas dynamic characteristics in the case of applying a thermal tool with electric discharge in other technologies of heat treatment and destruction of materials.